Efficient mode excitation and conversion in few-mode fiber for space-division multiplexing system / Lee Yen Sian - Lee , Yen Sian (2019)
Ever increasing demand on the transmission capacity of optical fiber communication network has led to the research interest in space-division multiplexing (SDM) technology. SDM has been deemed as a promising solution to expand the transmission capacity beyond the limit of ~100 Tb/s. It also aims to reduce the cost and energy consumption per bit of information being transmitted. Generally, there are two main approaches to SDM: (i) mode-division multiplexing (MDM) that employs the orthogonal spatial modes in few-mode fiber (FMF) and (ii) core multiplexing (CM) that employs spatially separated cores in a multi-core fiber (MCF). The key components for the implementation of the SDM by these approaches are the optical fibers, amplifiers and (de)-multiplexers. This thesis focuses on the investigation of mode conversion and polarisation manipulation in FMF that can find useful applications in the (de)-multiplexers of MDM. Firstly, LP01 → LP11 mode conversion and selective excitation in FMF by a tilted binary phase plate (BPP) were investigated. It was demonstrated in this work that a tilted BPP can enable efficient LP01 → LP11 mode conversion and excitation at operating wavelength longer than the design wavelength of the BPP. A method based on the peak intensity difference of the lobes in a LP11 mode profile has been proposed to estimate the LP01:LP11 ratio of the mode profile recorded at the FMF output. Next, effect of the two-mode fiber (TMF) output facet angle on the output beam profile was investigated via simulation. Simulation has shown that output facet angle close to the critical angle of the fiber can convert the LP11 mode in the fiber into a single-lobe beam at the fiber output. Based on the simulation result, a simple and low cost LP11 → LP01 mode converter made from an angled-facet TMF (AFTMF) has been demonstrated experimentally. Following that, LP01 and LP11 modes were simultaneously excited in a TMF by core-offset splicing technique and the output of the TMF was spliced to a three-paddle two-mode fiber polarisation controller (TMPC). The output beam of the TMPC was split by a polarising beam splitter (PBS). By tuning the paddles of the TMPC, it was observed at the PBS outputs that the LP01 and LP11 modes can be simultaneously aligned into two perpendicular polarisation states and split by the PBS. The mode profile and power at the PBS outputs were measured to evaluate the polarisation manipulation performance of the TMPC. Modal decomposition by numerical method was used to determine the modal purity of the mode profile. In addition, the stability of the mode purity, profile and power was analysed.